Principles and practice of analytical techniques in geosciences - Grice, Kliti (Royal Society of Chemistry, 2014)
The pace of revolution in analytical chemistry in the field of Geosciences has been dramatic over the recent decades and includes fundamental developments that have become common place in many related and unrelated disciplines. The analytical tools (nano to macro-scale from stable to radioactive isotopes to synchrotron imaging) used have been applied to wide-ranging applications from inorganic to organic geochemistry, biodiversity and chronological tools, to build an understanding of how the Earth system evolved to its present state.